Strategies, choices, and program priorities for the Eastern Africa Root Crops Research Network - Ntawuruhunga, Pheneas (International Institute of Tropical Agriculture, 2010)
EARRNET is one of the ASERACA networks whose mandate is research for development on cassava. Thefirst and second phases of the network’s activities were mostly characterized by biological research. Duringthe second phase, there was an emphasis to shifting to post-harvest and market issues. For that reason,EARRENT redefined its strategic vision and mission as “Transforming cassava into a broad-based commercialcommodity for sustained food security, poverty alleviation, and income generation through integrated regionalproduction, utilization, marketing, and trade”. In order to respond to this vision, the priority setting exercise wasconducted with stakeholders across the cassava sub-sector including representatives from traders, feed millers,farmers, NGOs, policy makers, Universities, and NARS, with special technical inputs provided by ASARECAand IITA. The ASARECA NARES’ socio-economists actively participated in the various workshops and helpedin providing the Priority Setting Committee with national data. The exercise that took place at ILRI, Nairobi,23–28 June 2003 followed the following steps:Step 1: Establishing the Network Committee for Priority SettingStep 2: Review of the Research DomainStep 3: Constraints and Opportunity AnalysisStep 4: Evaluation of Existing ResultsStep 5: Defining Research ThemesStep 6: Priority Setting of Research ThemesStep 7: Recommendations for Implementationfirst and second phases of the network’s activities were mostly characterized by biological research. Duringthe second phase, there was an emphasis to shifting to post-harvest and market issues. For that reason,EARRENT redefined its strategic vision and mission as “Transforming cassava into a broad-based commercialcommodity for sustained food security, poverty alleviation, and income generation through integrated regionalproduction, utilization, marketing, and trade”. In order to respond to this vision, the priority setting exercise wasconducted with stakeholders across the cassava sub-sector including representatives from traders, feed millers,farmers, NGOs, policy makers, Universities, and NARS, with special technical inputs provided by ASARECAand IITA. The ASARECA NARES’ socio-economists actively participated in the various workshops and helpedin providing the Priority Setting Committee with national data. The exercise that took place at ILRI, Nairobi,23–28 June 2003 followed the following steps: